Short-term exposure to particulate matter (PM10 and PM2.5), nitrogen dioxide (NO2), and ozone (O3) and all-cause and cause-specific mortality: Systematic review and meta-analysis - Orellano, Pablo; Reynoso, Julieta; Quaranta, Nancy; Bardach, Ariel; Ciapponi, Agustin (Environment international, 2020)
[Display omitted] •PM10, PM2.5, NO2 and O3 are common air pollutants which can affect human mortality.•Short-term associations with all-cause and cause-specific mortality were evaluated.•We performed a systematic review and meta-analysis of time-series studies.•We found positive associations for PM10, PM2.5, NO2, and O3 and all-cause mortality.•Associations were also positive between PM10 and PM2.5 and cause-specific mortality. Air pollution is a leading cause of mortality and morbidity worldwide. Short-term exposure (from one hour to days) to selected air pollutants has been associated with human mortality. This systematic review was conducted to analyse the evidence on the effects of short-term exposure to particulate matter with aerodynamic diameters less or equal than 10 and 2.5 µm (PM10, PM2.5), nitrogen dioxide (NO2), and ozone (O3), on all-cause mortality, and PM10 and PM2.5 on cardiovascular, respiratory, and cerebrovascular mortality. We included studies on human populations exposed to outdoor air pollution from any source, excluding occupational exposures. Relative risks (RRs) per 10 µg/m3 increase in air pollutants concentrations were used as the effect estimates. Heterogeneity between studies was assessed using 80% prediction intervals. Risk of bias (RoB) in individual studies was analysed using a new domain-based assessment tool, developed by a working group convened by the World Health Organization and designed specifically to evaluate RoB within eligible air pollution studies included in systematic reviews. We conducted subgroup and sensitivity analyses by age, sex, continent, study design, single or multicity studies, time lag, and RoB. The certainty of evidence was assessed for each exposure-outcome combination. The protocol for this review was registered with PROSPERO (CRD42018087749). We included 196 articles in quantitative analysis. All combinations of pollutants and all-cause and cause-specific mortality were positively associated in the main analysis, and in a wide range of sensitivity analyses. The only exception was NO2, but when considering a 1-hour maximum exposure. We found positive associations between pollutants and all-cause mortality for PM10 (RR: 1.0041; 95% CI: 1.0034–1.0049), PM2.5 (RR: 1.0065; 95% CI: 1.0044–1.0086), NO2 (24-hour average) (RR: 1.0072; 95% CI: 1.0059–1.0085), and O3 (RR: 1.0043; 95% CI: 1.0034–1.0052). PM10 and PM2.5 were also positively associated with cardiovascular, respiratory, and cerebrovascular mortality. We found some degree of heterogeneity between studies in three exposure-outcome combinations, and this heterogeneity could not be explained after subgroup analysis. RoB was low or moderate in the majority of articles. The certainty of evidence was judged as high in 10 out of 11 combinations, and moderate in one combination. This study found evidence of a positive association between short-term exposure to PM10, PM2.5, NO2, and O3 and all-cause mortality, and between PM10 and PM2.5 and cardiovascular, respiratory and cerebrovascular mortality. These results were robust through several sensitivity analyses. In general, the level of evidence was high, meaning that we can be confident in the associations found in this study.